Changes in microplanktonic protists assemblages promoted by the thermocline induced stratification around an oceanic archipelago - COSTA,ALEJANDRO E.S.F. DA (2018)
Abstract In the area around the archipelago of São Pedro e São Paulo (ASPSP), a set of small rocky islands in the Equatorial Atlantic, the thermocline begins at a more superficial depth than in the surrounding waters. This raises the question if there is any change in heterotrophic microplanktonic protists assemblages occurring in the surface mixed layer and in the subsurface layer. To answer this question, we sampled seawater in seven depths (between 1-100 m) with a 10L Niskin bottle and obtained temperature and salinity profiles with a CTD at eight sites around the ASPSP. The depth of the surface mixed layer varied between 18-63 meters. Dinoflagellates dominated in terms of abundance representing over 80% and 65% of the individuals found in the surface and subsurface layers, respectively. A PERMANOVA test revealed significant differences (p < 0.001) among the dinoflagellate and tintinnid assemblages occurring in both layers, but no evidence for difference in the radiolarian assemblage was detected. Good ecological indicators were found mainly within the dinoflagellate assemblage. The thermocline induced stratification allowed the development of different microplanktonic protists assemblages above and under the depth of the surface mixed layer in the upper 100 m of the water column.